Mechanical Affective Touch Therapy for Anxiety Disorders: Feasibility, Clinical Outcomes, and Electroencephalography Biomarkers From an Open-Label Trial - Carpenter, Linda L.; Kronenberg, Eugenia F.; Tirrell, Eric; Kokdere, Fatih; Beck, Quincy M.; Temereanca, Simona; Fukuda, Andrew M.; Garikapati, Sahithi; Hagberg, Sean (Frontiers in Psychiatry, 2022)
Abstract Background: Most external peripheral nerve stimulation devices designed to alter mood states use electrical energy, but mechanical stimulation for activation of somatosensory pathways may be harnessed for potential therapeutic neuromodulation. A novel investigational device for Mechanical Affective Touch Therapy (MATT) was created to stimulate C-tactile fibers through gentle vibrations delivered by piezoelectric actuators on the bilateral mastoid processes. Methods: 22 adults with anxiety disorders and at least moderate anxiety symptom severity enrolled in an open-label pilot trial which involved MATT self-administration using a simple headset at home at least twice per day for 4 weeks. Resting EEG data were acquired before and after a baseline MATT session and again before the final MATT session. Self-report measures of mood and anxiety were collected at baseline, week 2 and week 4, while interoception was assessed pre- and post-treatment. Results: Anxiety and depressive symptoms improved significantly from baseline to endpoint, and mindfulness was enhanced. EEG metrics confirmed an association between acute MATT stimulation and oscillatory power in alpha and theta bands; symptom changes correlated with change in some metrics. Conclusion: Open-label data suggest MATT is a promising noninvasive therapeutic approach to anxiety disorders that warrants further development.